Effect of corporate social responsibility on dividend payout of listed firms in ghana: the role of firm size - GALLEY WISDOM (KNUST, 2024)
A thesis submitted to the department of accounting and finance, college of humanities and social sciences, in partial fulfillment of the requirements for the award of the degree of master of science in accounting and finance